Management of Recurrent Fistula-in-Ano (Bhagandara) Extending upto Thigh, by Partial Fistulectomy and Ksharasutra Application: A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
In the present modern day's world, anorectal disorders are increasing in number due to sedentary lifestyle. They cause great discomfort and make one’s life miserable. Among these fistula in ano is most common. It is challenging to treat due to its recurrent nature. Fistula-in-ano is an inflammatory tract that is lined by unhealthy granulation tissue and has two openings, an external opening present in perianal skin and an internal opening in the anal canal or rectum. Fistula in ano is correlated with Bhagandara in Ayurveda. Acharya Sushruta has mentioned it among Ashta Mahagada and explained five types of Bhagandara. Many treatment modalities have been given for the treatment of fistula in ano, Ksharasutra application is one of them. It is a minimally invasive para-surgical procedure and induces both mechanical as well as chemical cutting and healing of the fistulous tract. This technique has a high success rate but it is time-consuming and causes minimal complication. A 73 years old male patient came to RGGPG Ayurvedic College and Hospital, with a complaint of pain and pus discharge from his left thigh for 7-8 years, he has been diagnosed with a case of recurrent fistula in ano. The patient was treated with partial fistulectomy along with Ksharsutra application and recovered well with complete excision of the tract.